MAGNETIC SUSCEPTIBILITY OF THE SURFACE SEDIMENTS OF LAKE BAIKAL AND LAKE BIWA - Sakai H.; Nomura Sh.; Araki S.; Kashiwaya K.; Tani Y.; Shibata Y.; Kawai T.; Kravchinskii V.A.; Peck J.; King J. (My University, 2001)
Magnetic susceptibility was studied on short sedimentary cores (a few meters) from lakes Baikal and Biwa. Measurements of cores less than 1 m long showed that the Baikal samples have oblate anisotropy ellipses with nearly vertical short axes, whereas in the Biwa cores these axes are nearly horizontal and their oblate geometry is poorly pronounced. The difference in anisotropy of magnetic susceptibility of the cores from the two lakes may be due to different depositional environments (water depth at the sampling site in Baikal was 200 to 1600 m, and that in Biwa was a few tens of meters). The magnetic susceptibility anisotropy increases down the cores and reaches a stable value at a certain depth. It shows a direct correlation with variations in water depth at sampling sites. The hydraulic pressure on the bottom sediments may be related to the depth of magnetic susceptibility saturation. Magnetic susceptibility of the Ver-99 gravity core recovered on the opposite side of Lake Baikal in the Selenga pro-delta varies broadly in the age region of 11 to 12 ka, and anisotropic parameters show the same changes within these age intervals. The magnetic susceptibility of the Ver-97 st. 6 gravity core from the Akademichesky Ridge exhibits similar variations. The succession of magnetic susceptibility fluctuations is possibly related to the cooling event of Younger Dryas (11 to 12 ka BP). At that stage, a significant sediment transport may have occurred over a great area of Lake Baikal. The age-dependent fluctuations in magnetic susceptibility in the Ver-97 core show a nearly perfect correlation with variations in δ18O in oceanic records, though the response of magnetic susceptibility is stronger at the interglacial boundary. This means that the glacial-interglacial transition on the continent (Lake Baikal) may have been more rapid than that in the ocean.